Is nonabsorbable nasal packing after septoplasty essential? A meta‐analysis. (30th November 2016) - Kim, Jong Seung; Kwon, Sam Hyun
Abstract : Objectives: Septoplasty is one of the most frequently performed rhinologic surgeries. Complications include nasal bleeding, pain, headache, septal hematoma, synechia, infection, residual septal deviation, and septal perforation. In this study, we aimed to compare complication rates among patients according to packing method. Methods: We performed a literature search using PubMed, Embase, and the Cochrane Library through August 2016. Our systematic review followed Preferred Reporting Items for Systematic Reviews and Meta‐analyses guidelines. Random effect models were used to calculate risk differences and risk ratio with 95% confidence intervals (CIs). Cases referred to the nonpacking group included patients treated with transseptal sutures or septal splints. Cases referred to as the packing group included patients treated with nonabsorbable packing such as Merocel or gauze. Results: Our search included 20 randomized controlled trials (RCTs) with a total of 1, 321 subjects in the nonpacking group and 1, 247 subjects in the packing group. There were no significant differences between packing methods regarding bleeding, hematoma, perforation, infection, and residual septal deviation. The risk differences of postoperative pain, headache, and postoperative synechia were −0.50 [95% CI: −0.93 to −0.07, P = .02], −0.42 [95% CI: −0.66 to −0.19, P = .0004], and −0.03 [95% CI: −0.06 to −0.01, P = .01], respectively. Conclusions: Nonabsorbable nasal packing is no more effective than treatments without packing after septoplasty. Septal splints and transseptal sutures reduce postoperative pain, headache, and synechia. Level of Evidence: 1B Laryngoscope, 127:1026–1031, 2017